Solvent Induced Helix Folding of Defined Indolenine Squaraine Oligomers - Turkin, Arthur; Holzapfel, Marco; Agarwal, Mohit; Fischermeier, David; Mitric, Roland; Schweins, Ralf; Gröhn, Franziska; Lambert, Christoph (Chemistry - A European Journal, 2021)
A protecting group strategy was employed to synthesise a series of indolenine squaraine dye oligomers up to the nonamer. The longer oligomers show a distinct solvent dependence of the absorption spectra, that is, either a strong blue shift or a strong red shift of the lowest energy bands in the near infrared spectral region. This behaviour is explained by exciton coupling theory as being due to H- or J-type coupling of transition moments. The H-type coupling is a consequence of a helix folding in solvents with a small Hansen dispersity index. DOSY NMR, small angle neutron scattering (SANS), quantum chemical and force field calculations agree upon a helix structure with an unusually large pitch and open voids that are filled with solvent molecules, thereby forming a kind of clathrate. The thermodynamic parameters of the folding process were determined by temperature dependent optical absorption spectra.
CRIS-Team Scopus Importer:2021-05-21
Keywords: dye chemistry; solvent effects; superstructure; supramolecular folding; UV/Vis spectroscopy